Lymph Nodes Metastasis is Associated with Higher Body Mass Index in Indonesian Breast Cancer Patients - Yournita, Debbie; Rustamadji, Primariadewi (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
Background Breast cancer is the most prevalent malignancy among women and is the second largest contributor to cancer-related deaths globally. Women with a high body mass index (BMI) are at a greater risk of developing breast cancer and an increased risk of lymph node metastasis. This retrospective study aimed to determine the relationship between BMI and the clinical pathological profile of invasive breast carcinoma (IBC) patients. Method This study was conducted from 2019 to 2022. Data were collected through the archives of the Department of Anatomic Pathology FKUI/RSCM (Faculty of Medicine, University of Indonesia/Cipto Mangunkusumo Hospital). Clinical pathological data were collected. The histological type, grade, lymphovascular invasion, and lymph node metastasis of the tumors were re-evaluated. The chi-square hypothesis test was used to determine the relationship between BMI and clinical pathological profile. The results were considered statistically significant with a p <0.05. Result A total of 151 cases of IBC with lymph node dissection from 2019 to 2022 were included in this study, all of which were female, with the majority being >50 years old (55%). The most common tumor size and histological type were T2 (39,7%) and invasive ductal carcinoma NST (74,8%), 49% of cases were grade 3 tumors. Most IBC cases had an obese BMI (49%), 63.1% with lymph node metastasis had an overweight-obese BMI. Statistical analysis was performed between BMI and lymph node metastasis status, and p-value=0.025 was obtained. The relationship between tumor size and lymphovascular invasion with lymph node metastasis was also found to be statistically significant, as indicated by a p-value of 0.000. Conclusion Cases with lymph node metastasis had the highest rate of overweight-obesity, and a significant relationship was found between BMI and lymph node metastasis status. A significant relationship was also found between tumor size and lymphovascular invasion with lymph node metastasis.